Comparative Efficacy and Safety of Oral zinc Sulphate Versus Cryotherapy in the Treatment of Viral Warts - Begum, Sharmin; Wahab, Md Abdul; Karim, Md Nazmul; Khondker, Lubna (Community Based Medical Journal, 2017)
Viral warts are a common problem in dermatology. Viral warts have a considerable negative effect on a patient's quality of life; although the rate of spontaneous recovery is high, it usually takes a long time and some patients might not show this spontaneous healing. A clinical trial was carried out to evaluate and compare the efficacy of oral zinc sulphate and cryotherapy in patients with viral warts. The study was conducted in the Department of Dermatology and Venereology, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh for duration of July 2015 to December 2015. Total sixty patients were enrolled and divided into group A and group B. Thirty of group A patients was treated by cryotherapy and thirty of group B patients was treated by oral zinc sulphate. Improvement rate was highest for the lesions on the finger, which is 18 (34.6%) and lowest for scalp 03 (5.8%). Improvement rate for palm 17 (32.7%); for foot 10 (19.2%) and toe 04 (7.7%). Out of all respondents from Group-A, the mean size of the lesions were 8.17mm, 5.90 mm, 4.32 mm and 3.57 mm at before treatment and 1st visit, 2nd visit and 3rd visit after treatment respectively. In Group-B, the mean size of the lesions were 7.50 mm, 4.92 mm, 3.00 mm, and 4.75 mm at before treatment and 1st visit, 2nd visit and 3rd visit after treatment respectively. Among the respondents of group-A & B, 27 (90%) and 25 (83.3%) were improved respectively. No statistical significant difference was observed between the two groups. Both cryotherapy and oral zinc sulphate when used individually were found to be equally effective in the treatment of viral warts but cryotherapy was found to be superior in efficacy. CBMJ 2017 January: Vol. 06 No. 01 P: 17-23